(untitled) (Slavic Studies, 2024)
This article presents various studies on idiomatic translation. It presents the views of a number of Czech linguists and theorists of translation, as well as of translators from other countries. The translation of idiomatic expressions requires thorough knowledge of both languages and cannot always be translated by means of finding full equivalents.